Community perspectives on the reintroduction of Eurasian lynx (Lynx lynx) to the UK. Issue 6 (18th October 2020) - Hawkins, Sally A.; Brady, Deborah; Mayhew, Michael; Smith, Darrell; Lipscombe, Steven; White, Chris; Eagle, Adam; Convery, Ian
Abstract : The potential for the reintroduction of Eurasian lynx ( Lynx lynx) to the UK gained considerable attention in 2017 when the Lynx UK Trust announced their intention to apply for a license to hold a controlled trial reintroduction of lynx in Kielder Forest, Northumberland, an application which was denied in 2019 by the then Secretary of State Michael Gove MP. The historical extirpation of large carnivores in the UK has resulted in communities, populations, and landscapes with little or no experience of coexistence with large predators. While charismatic carnivores have significant cultural symbolism and are often promoted as flagship species for conservation and rewilding, their reintroduction presents challenges for conservation and rewilding in practice, not least in terms of managing often vehement opposition. This article presents findings from the initial consultation process and considers the lessons learned from the methodological approach. In particular, while the incomplete consultation centered on a community‐based approach, there were several factors that constrained public participation, information sharing, and transparent communications integral to this. These are identified and explored here using qualitative data collected during the local consultation, with the intention of informing any similar reintroduction projects.